Konflik Antar Warga di Tanjung Balai Asahan Sumatera Utara - Heni Ismiati; Muhammad Fedryansyah (Jurnal Empirika, 2017)
Conflicts in Tanjung Balai Asahan involving cultural violence. A conflict begins with the construction and placement of the Amithaba Buddha statues at the monastery Tri Ratna who are considered Muslims Tanjung Balai disturbing the comfort of their worship. Then there was the burning of the monastery took place on July 29, 2016, involving cultural sentiment. Related cultural community sentiment is due to the assumption that the existence of differences that could not be put together between the Malay Tanjung Balai versus ethnic Chinese. According to (Galtung, 1990), this cultural violence is violence that includes and is one of the roots of violence and structural violence directly. Cultural violence is an aspect of culture including religion and ideology, language, arts, science, and symbol-symbol of culture as myth, the concept eventually led to certain cultures, which is then the value in the culture that made the justification by the community against acts of violence or conflict. The Community will be no encouragement of manipulation and provocateur who utilize this condition so that there are issues that can be resolved to base became manifest and uncontrolled. Therefore, the harmonization within the community should be made, for instance by holding mutual charity program and thus the intermingling in the society.